Interface of Linguistics, Literature, and Culture in Translating Singapore and Sri Lanka Postcolonial Poetry - Novita Dewi (Lingua Cultura, 2016)
The interface of linguistics, literature, and culture was clear in translation. English Studies in Indonesia had undergone revision by the inclusion of postcolonial literature in its curriculum. Literary works from Malaysia, Singapore, Philippines, Sri Lanka, India and other Asian countries were introduced and translated. Given that language game was central in postcolonial writing, equitable knowledge and grasps of linguistics, literature, and culture were significant in translation. Through the lens of re-placing language as textual strategies in post-colonial writing, this paper explored the application of this reading method and gave practical examples of translating English poems written in, respectively, Singapore and Sri Lankan postcolonial contexts into Indonesian. The discussion showed that in order to preserve the postcolonial strategies of writing back to the colonial ideology, the translation took into account the reconceptualization and reconstruction of people, language, and culture, instead of literal rendering from the source language to the target language. Adoption of postcolonial theory as the translating method shown in this study is important to add to the theory and practice of translation. This trajectory can be used to translate other literary works written in varieties of English into Indonesian, using as they do, different translation strategies to make the translation products accurate, appropriate, and acceptable.